Stress and Maladaptive Psychological Responses as Predictors of Postpartum Depression - Faujiah, Irfa Nur; Ambari, Alvin Alvani Tresna; Saefudin, Muhamad Arif (Journal of Maternal and Child Health, 2025)
Background: Unmanaged stress and maladaptive psychological responses during the postpartum period increase the risk of postpartum depression, highlighting the need for evidence-based interventions in primary health care. This study aimed to analyze the influence of stress levels and psychological adjustment difficulties as risk factors for postpartum depression among mothers in the Singaparna Primary Health Care area.Subjects and Method: A cross-sectional study was conducted in five villages within the Singaparna Primary Health Care. A total of 150 postpartum mothers were recruited purposively. The independent variables were stress levels and psychological adjustment. The was dependent variable was postpartum depression. Data on stress were collected usng the Perceived Stress Scale (PSS-10). Psychological adjustment was measured using the Postpartum Adjustment Questionnaire (PAQ-15).  Postpartum depression was assessed using the Edinburgh Postnatal Depression Scale (EPDS). Reliability and construct validity were confirmed, and Structural Equation Modeling (SEM) was applied to assess predictive relationships.Results: Maladaptive stress responses significantly reduced postpartum depression (β = 0.54, p= 0.002), Positive stress perception (β = 0.133, p= 0.302) and postpartum adjustment (β= 0.124, p= 0.159) were insignificantly associated. The SEM model showed acceptable fit (RMSEA= 0.06; CFI= 0.89; TLI = 0.88; SRMR= 0.07).Conclusion: Maladaptive stress responses are a key psychosocial risk factor for postpartum depression, whereas postpartum adjustment and positive stress perception show limited influence. Early screening and psychosocial interventions in primary care are essential to reduce postpartum depression and improve maternal mental health outcomes.